2022
DOI: 10.3390/nu14102110
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise and Nutritional Interventions on Body Composition in Patients with Advanced or Metastatic Cancer: A Systematic Review

Abstract: Advanced and metastatic cancers significantly alter body composition, leading to decreased lean mass and variable effects on fat mass. These effects on body composition are associated with significant physical dysfunction and poor prognosis in patients with cancer. Whilst exercise and nutritional interventions are likely to be of benefit in counteracting these effects, relatively little is known about using such interventions in patients with advanced or metastatic cancer. Therefore, in this systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…Our results reveal a clinically meaningful change in body composition following exercise in all patients with bone metastases, but no signi cant difference when compared to the usual care group. It is similar to Barnes et al [32]. They found that even simple activities, like walking, could stop the loss of lean body mass in people with advanced cancer.…”
Section: Discussionsupporting
confidence: 85%
“…Our results reveal a clinically meaningful change in body composition following exercise in all patients with bone metastases, but no signi cant difference when compared to the usual care group. It is similar to Barnes et al [32]. They found that even simple activities, like walking, could stop the loss of lean body mass in people with advanced cancer.…”
Section: Discussionsupporting
confidence: 85%
“…Age, sex and inherited genes are predisposing factors for variation in VAT accumulation [33,40]. Other than the above nonmodifiable factors, physical activity and dietary patterns are modifiable and provide economically, noninvasive and nonpharmacological approaches for VAT reduction and body composition improvement [41]. Hence, following visceral identification, immediate lifestyle intervention is beneficial to these cancer patients in terms of both surgical outcomes and cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most interventions have been developed for use in breast, prostate, and colorectal cancer survivors, 9,10 and may not be generalizable to individuals undergoing active cancer treatment or to survivors of other types of cancer such as hematologic cancers. Interventions have generally focused exclusively on nutrition and/or exercise, 11 which may not always align with patient goals and do not routinely address barriers to physical activity such as symptom burden. 12 In light of the limitations of existing interventions, we developed a novel theory-based intervention utilizing patient-generated health data (PGHD) called the HealthScore Health Coaching Program (HealthScore).…”
Section: Introductionmentioning
confidence: 99%